Identification of Cysteine 270 as a Novel Site for Allosteric Modulators of SARS‐CoV‐2 Papain‐Like Protease. Issue 52 (28th November 2022) - Hu, Hangchen; Wang, Qian; Su, Haixia; Shao, Qiang; Zhao, Wenfeng; Chen, Guofeng; Li, Minjun; Xu, Yechun
Abstract: The coronavirus papain‐like protease (PL pro ) plays an important role in the proteolytic processing of viral polyproteins and the dysregulation of the host immune response, providing a promising therapeutic target. However, the development of inhibitors against severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) PL pro is challenging owing to the restricted S1/S2 sites in the substrate binding pocket. Here we report the discovery of two activators of SARS‐CoV‐2 PL pro and the identification of the unique residue, cysteine 270 (C270), as an allosteric and covalent regulatory site for the activators. This site is also specifically modified by glutathione, resulting in protease activation. Furthermore, a compound was found to allosterically inhibit the protease activity by covalent binding to C270. Together, these results elucidate an unrevealed molecular mechanism for allosteric modulation of SARS‐CoV‐2 PL pro and provid a novel site for allosteric inhibitors design. Abstract : Two allosteric and covalent activators of SARS‐CoV‐2 papain‐like protease (PL pro ) were identified to elucidate a novel site, cysteine 270 (C270), which led to the discovery of an endogenous activator and an inhibitor of the protease. This study provides a paradigm for identifying covalent and allosteric sites and offers an opportunity for the development of SARS‐CoV‐2 PL pro inhibitors.